Herbal Medicine Practices of Patients With Liver Cancer in Peru: A Comprehensive Study Toward Integrative Cancer Management - Rojas Rojas, Teresa (2018)
Rationale: The highest burden of liver cancer occurs in developing countries, where the use of herbal medicine (HM) is still widespread. Despite this trend, few studies have been conducted to report HM practices of patients with a hepatic tumor in the developing world. Hence, this study aimed to document the use of HM among patients with liver cancer in Peru.